A novel high capacity space efficient heat storage system for domestic applications - Ramadan, Mohamed Elamin; Omer, Siddig; Riffat, Saffa (2016)
Energy consumption in domestic buildings is dominated by space heating 60 percent followed by hot water 14 percent in the UK. Space heating and water heating confers a disparate set of industrial challenges to the manufacture and this is a very demanding objective, which necessitates novelty. Space heating and water heating functions will become more significant as the trend towards low energy homes rises for a fully integrated system. The most common practical heat storage's are water and latent heat of fusion storage media. The new Thermochemical reaction materials regarded as most promising materials for the ability of store sufficient heat for practical domestic requirements. The volume capacities of materials play a key role for choosing storage system and this have a direct bearing on the performance of the heat storage system for domestic heating and heating water. Innovative thermal energy storage was conducted in a new concept for domestic applications at the Laboratory University of Nottingham, UK. An initial result has been investigated experimentally.